Economic Growth, People's Livelihood Preferences of Local Governments and Residents' Health - Cen, Shu-tian; Yan, Wei-hai (Frontiers in Public Health, 2022)
This article is aimed to examine the effect of economic growth on the health of residents from the perspective of local government behavior. First of all, it is theoretically proved that in an economy with economic decentralization and political centralization, because the local government implements the central planner's “people-oriented” and “people-centered” requirements, the local government pays attention to both its own consumption and the health of residents. For this reason, he prefers public health investment, and the conclusion is that there is a stable and balanced relationship between residents' health and economic growth. When the local government's relative importance to people's livelihood is greater than its own consumption, the economic growth will have a significant and positive impact on residents' health. And the internal mechanism of economic growth affecting residents' health is combed mathematically. Secondly, using panel data from China's 31 inland provinces from 2003 to 2019, empirical tests show that the hypothesis that China's economic growth promotes residents' health is established. The work of this article means that the improvement of residents' health depends not only on the total amount of available resources brought about by economic growth, but also on the government's livelihood preferences. The public health investment behavior of local governments in China is an important clue to explains that China's economic growth can promote residents' health.